ALTRUISME SEMU DI SEKOLAH: Analisis terhadap Praktek-praktek Kekerasan dan Keterlibatan School Stakeholder dalam Kegiatan Inisiasi Sekolah - Meredian Alam (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
For over decades in Indonesian public high school, freshmen orientation program in form of school initiation has been perceived as process that leads to altruistic behavior; consisted of solidarity, closely group interaction, deeper understanding on school’s living values, and internal norms. However, its implementation is currently raising many protests of educational experts and scholars as well as become a point of vocal in public areas because violent actions are profoundly practiced as ways to infitrate those altruism and potentially inflct another precedent thought that the activities could be alternative for individual’ growth in near future. Accordingly, this research conducted in one of public school in Yogyakarta province attempts to analyze the involvement of school stakeholders throughout the ongoing process in the school initiation and to identify why misleading concept of education remains applied by school’ stakeholders. Therefore, the fial recommendation of this research is subjected not only to the school stakeholders, but also relevant boards in the government, where the school aparatus should highly involve parents in making decision and implement accountable action in disseminating information pertinent to education process, the relevant board of education in governmental sector should also increase the partnership with local non-governmental organization who has areas of working in the peace and education to seek and design relevant alternative programs for the sake of eradicating violent actions in the school. Local community situated in the school’s surroundings should be also actively involved by respective schools for some of community development-related activities. The last mentioned recommendation is purposively to have students understand deeper and comprehend throroughly the use of knowledge that they learn at school for society.